Utilidad del apoyo con glutamina y arginina enteral (inmunonutrición) en el manejo de los pacientes con fístulas enterocutáneas postoperatorias - Martínez Ordaz, José Luis (Universidad Autónoma Metropolitana, 2012)
La sepsis es la principal causa de morbilidad y mortalidad de los pacientes con fistulas enterocutáneas (FEC). A pesar de que la inmunonutrición preoperatoria muestra menor incidencia de complicaciones infecciosas en pacientes quirúrgicos con cáncer gastrointestinal, no se han realizado estudios de la misma en pacientes con FEC. El objetivo del presente trabajo fue determinar el efecto de la administración enteral preoperatoria de glutamina y arginina en pacientes con FEC sometidos a tratamiento quirúrgico. Pacientes y métodos: durante un periodo de 24 meses, se intervinieron quirúrgicamente 40 pacientes con FEC para la resolución de la misma. Todos tenían al menos 100 cm de intestino delgado proximal a la fístula. Fueron divididos en dos grupos: el grupo control que se manejó con el esquema estándar preoperatorio y el grupo experimental que además recibió 10 g/d de glutamina y 4.5 g/d de arginina durante los 7 días previos a la cirugía. Las variables demográficas, de la enfermedad y quirúrgicas fueron recabadas de manera prospectiva. La variable de efecto primario fue la infección postoperatoria. Las variables secundarias incluyeron recurrencia de la FEC, la caracterización de la respuesta proinflamatoria durante la primera semana postoperatoria, curación total y mortalidad. Las comparaciones entre grupos fue realizada con la prueba de T de Student para las variables continuas y la prueba exacta de Fischer para las variables nominales. Resultados: Las variables demográficas, de enfermedad y quirúrgicas fueron similares entre los grupos. Siete pacientes desarrollaron infecciones posoperatorias en el grupo control y ninguno en el grupo experimental (p 0.05). Las concentraciones de citocinas pro inflamatorias durante la primera semana fueron significativamente menores en el grupo experimental. Este hallazgo fue más notorio en pacientes con infecciones o recurrencia. Conclusiones: la administración enteral preoperatoria de glutamina y arginina parecer tener efectos positivos en pacientes con FEC sometidos a tratamiento quirúrgico. Se observó una menor presentación de complicaciones infecciosas, recurrencia y mayor curación total en los pacientes que la recibieron; Sepsis remains as the main cause of morbidity and mortality in patients with enterocutaneous fistulas (ECF). Nonetheless that preoperative immunonutrition in patients with gastrointestinal malignancies submitted to operative treatment has shown less infectious complications (IC), no studies regarding use of this approach in patients with ECF have been conducted. Our aim was to assess the effects of preoperative enteral glutamine and arginine in patients with ECF who require surgical attempts for its closure. Patients and Methods: During a 24 month study period, 40 patients with ECF were operated for its resolution. All had at least 100 cm of proximal small bowel. They were assigned at either of 2 groups: patients in the control group (n=20) were managed with our standard preoperative protocol; patients in the experimental group (n=20) received oral glutamine (10 g/d) and arginine (4.5 g/d) preoperatively for 7 days. Patient, disease, and operative variables were prospectively collected. Our primary endpoint was IC. Secondary endpoints included ECF recurrence, definitive ECF healing and mortality, and characterization of pro-inflammatory cytokines (Interleukin 6 and C reactive protein) during the first postoperative week. Comparisons were made using Student’s t-test for continuous variables and Fischer’s exact test for categorical variables. Results: All patients, disease and operative variables were similar for both groups. IC developed in 7 and 0 patients in the control and the experimental group respectively (p˂0.01). Some patients in the control group had more than one IC and thus this difference became more evident when total number of complications 4 per group were calculated (14 vs 0 respectively, p˂0.01). Comparing secondary endpoints for patients in the control and experimental groups, ECF recurred in 11 and 2, respectively (p=0.001), and definitive ECF closure was achieved in 10 and 19, respectively (p ˂0.01). Two patients in the control group and 1 in the experimental group died (p >0.05). Levels of pro-inflammatory cytokines were significant lower in patients from the experimental group compared to the control group. This finding was more evident in patients who had infectious complications and recurrence. Conclusions: Use of preoperative enteral glutamine and arginine seems to provide beneficial effects for patients with ECF submitted to operative treatment. There were less number of total IC and a clear tendency towards less number of patients with IC, less ECF recurrence and more definitive ECF closure and healing